Perancangan Interior Resto Edukasi Masakan China di Surabaya - Utama, Elisabeth Kristina (Intra, 2013)
Restaurant is one alternative place that aims to meet the primary needs of human beings which is eating. Nowadays, eating is no longer just a necessity but also as a hobby so that the term "culinary tourism". Educational Resto Chinese cuisine comes to fulfill the wishes of the people. In addition to providing a new culinary experience also gives a brief insight about Chinese cuisine. Existing facilities at the educational resto is receptionis, waiting room, open kitchen area where visitors can interact directly with the other chefs, cooking class that teaches how to cook good Chinese cuisine and VIP room that provides facilities called Private Dining Experience. According to the type of cuisine that served, the restaurant is embracing the concept of symmetry, which is one characteristic of the Chinese style.